Thrombin Physiology and Disease - Maragoudakis, Michael E.; Tsopanoglou, Nikos E. (Springer New York : Imprint: Springer, 2009)
It has become increasingly evident in recent years that, apart from the key role that thrombin plays in the blood coagulation cascade, thrombin also elicits cellular actions via the activation of proteinase-activated receptors, which are present in many cell types. These effects of thrombin are seen in a variety of physiological as well as pathological phenomena, including vascular development and physiology, tumor progression and metastasis, neuronal functions, inflammation, angiogenesis. Thrombin: Physiology and Disease, edited by Michael E. Maragoudakis and Nikos E. Tsopanoglou, emphasizes the new developments in this important field of research and provides the basis for translating these findings into therapeutic targets.".